Analysis of the Pile-Soil Combined Effect of Micropiles in Strengthening Expansive Soil Landslide in Southern Shaanxi Based on the Dynamic Soil Arch Model. (14th November 2022) - Ding, Xiao; He, Hui; Qu, Yonglong; Yang, Yixuan
Abstract : Southern Shaanxi region is mountainous and landslide disasters are frequent. Micropile reinforcement technology is widely used in landslide management, especially in landslide emergency rescue projects, due to easy construction, small soil disturbance, and strong site adaptability. Soil arch effect is an important prerequisite for safe and economic performance of the support function of micropile. For the swelling soil landslide of the accumulation layer in southern Shaanxi, firstly, a numerical model is established by means of thermal-mechanical coupling of FLAC 3D to explore the variation of the soil arch form with different swelling forces. Then, two theoretical models are proposed under normal working condition and rainfall working condition. The evolution and failure mode of soil arch are analyzed. The results show that the soil expansion after rainfall causes the change of the soil arch mode, the range of pile-soil interaction is obviously reduced, and the soil arch effect is weakened. It should be considered in the design of micropiles in strengthening expansive soil landslide.